7,12-Dimethylbenz(a)anthracene as a Model for Ovarian Cancer Induction in Rats - Ana Carolina Ciseski Gonçalves; Katia Candido Carvalho; José Antônio Orellana Turri; Ricardo dos Santos Simões; Jesus Paula Carvalho; Luiz Fernando Ferraz da Silva; José Maria Soares Júnior; Edmund Chada Baracat (Biology)
Ovarian cancer has the highest mortality rate of all gynecological cancers. Animal models using 7,12-dimethylbenz(a)anthracene (DMBA) have been developed to investigate the mechanisms of ovarian carcinogenesis. The present study is a systematic review of efforts to establish DMBA as a model for ovarian cancer induction in rat models. A total of 432 studies were retrieved from the Medline/PubMed and Embase databases. The studies using DMBA to induce ovarian cancer with isolated results were included in our analysis, and their data were meta-analyzed. The ROBINS-I tool and a meta-analysis demonstrated a low risk of bias (less than 1%) for increased effectiveness and no bias for mortality. The results were all similar: regardless of the dose, administration route, animal strain, or induction time, the induction rate of ovarian tumors was always high, reinforcing the role of DMBA as an effective inducer of ovarian carcinogenesis. We conclude that ovarian carcinogenesis can be studied using DMBA as an inducer in rat and mouse models with a long time range for tumor establishment (at least 110 days) and a high rate of mortality. CNPq (No. 304264/2021-0) and FAPESP (Protocol No. 2018/24224-9).